Learning Environment An Intrinsic Motivational Approach - SHUKLA, RUCHI (JOURNAL OF INDIAN EDUCATION, 2017)
The lack of fun in learning process has resulted in learning becoming a forced, extrinsically driven activity in contrast to the earlier fun-filled years of learning and growing. Children by nature are intrinsically motivated to learn; this is because they want to learn about the surroundings they live in so that they can deal effectively with the environment. The intrinsic motivation to learn also exists because children want to know about themselves, develop a sense of self-efficacy in order to effectively handle and manipulate the environment. However, this natural curiosity or intrinsic motivation in the child often remains curbed and results in a disinterested student at school. Social psychological impact of educational load and current problems with early childhood education can be understood within the existing psychological theories of personality and motivation. A theory which has been specifically found to be suitable for educational context is Ryan and Deci’s Self-determined Theory (SDT). To differentiate autonomous from controlled intentions, Deci (1980) adopted the term self-determination (in contrast to intentions that were externally determined, reward determined, guilt determined, etc.). Analysis of the relationship between schooling experiences and parental expectations and the experience of educational stress can be understood in the SDT framework in which sense of autonomy, self-efficacy or competence and relatedness can be said to affect the degree of internalisation of the motivation for school-related performance which in turn would be related to experiencing educational stress.